Developing EFL Students’ Writing Ability Through Contextual Teaching and Learning (A Classroom Action Research Study) - Adolfina M. S. Moybeka; Fabianus Hadiman Bosco; Corneles Rubenaser Apalem; Detri Amelia Chandra; Efendi Efendi (Journal of English Culture, Language, Literature and Education, 2023)
Writing ability is an ability that refers to the notion of knowledge and understanding of writing. Judging from language skills, writing is an active productive activity, namely the activity of producing language and writing activity is also a form of realization of abilities and skills in the most recent language mastered by language learners after listening, speaking, and reading skills. Seeing the importance of this writing skill, the purpose of this study is to see the effectiveness of the CLT method in improving students' descriptive text writing skills. In its application, the researcher used CAR. In this study there were 20 students of SMA PGRI Kalabahi in the academic year 2022/2023. The data of this study were obtained from students' writing tests. As a result of the research, the CLT method has a significant impact on students' writing ability. In addition, the supporting factors of learning success include the use of props to write descriptive text and the teacher's proficiency in applying the contextual approach. Meanwhile, the inhibiting factors were students' lack of knowledge about descriptive text, their lack of ability and enthusiasm in stringing words to create descriptive text, students' low interest in descriptive text writing activities, as well as students' enthusiasm and unsupportive play environment. The application of contextual approach was able to develop students' descriptive text writing ability seen from the results of students' descriptive text writing, students' interest and response in following the learning of descriptive text writing by using contextual teaching and learning method.